Financial Literacy and Business Management for Women Entrepreneurs: An Empowerment Program in Urban Communities - Aripin (Global Writing Academica Researching and Publishing, 2024)
The Women Entrepreneur Empowerment Program is a strategic effort to increase independence and business success in urban communities. This research aims to evaluate the effectiveness of an empowerment program that focuses on financial literacy and business management skills for women entrepreneurs in the Jakarta Womenpreneur Community. The research methodology uses a quantitative research design with a sample of 120 participants. The research results showed significant improvements in basic understanding of finance, use of financial tools, financial planning, business planning, leadership skills, time management, and use of technology in business after attending the program. The research results show that a holistic and responsive approach to individual needs and challenges can increase the independence and business success of women entrepreneurs in urban communities. By providing relevant and sustainable knowledge, skills and support, this empowerment program provides a significant positive impact and has the potential to become an important instrument in creating an inclusive and sustainable business ecosystem.